2017
DOI: 10.1186/s12936-017-1792-1
|View full text |Cite
|
Sign up to set email alerts
|

Defining micro-epidemiology for malaria elimination: systematic review and meta-analysis

Abstract: BackgroundMalaria risk can vary markedly between households in the same village, or between villages, but the determinants of this “micro-epidemiological” variation in malaria risk remain poorly understood. This study aimed to identify factors that explain fine-scale variation in malaria risk across settings and improve definitions and methods for malaria micro-epidemiology.MethodsA systematic review of studies that examined risk factors for variation in malaria infection between individuals, households, clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 64 publications
1
47
0
1
Order By: Relevance
“…Variation in this index is observed within the road accessible localities, but not within the river accessible households, due to the constraints above described. Housing construction quality is a proxy for wealth in several studies of malaria risk factors, as reviewed by Bannister-Tyrrell et al [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in this index is observed within the road accessible localities, but not within the river accessible households, due to the constraints above described. Housing construction quality is a proxy for wealth in several studies of malaria risk factors, as reviewed by Bannister-Tyrrell et al [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…between households or other sub-village groupings within villages, or between neighbouring villages or other similar socio-spatial aggregations such as urban neighbourhoods, agricultural settlements and health centre catchment areas? [ 14 ]. The household survey described here is a micro-epidemiology study conducted in the Juruá hotspot to investigate the distribution of malaria and its interaction with socio-economic, behavioural and demographic parameters along gradients of development.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the patterns of endemicity observed in these populations suggested that prevention efforts should be population specific, and vary according to the epidemic characteristics exhibited by the parasite in the targeted population. Demographic, social and population factors confound studies limited to environmental factors and are also excluded from many studies [ 87 ] and thus could hold important insight on malaria control. We are currently experiencing an epidemic transition in malarial infection in Colombia, where parasite loads in populations are being transformed (potentially as populations are also subject of change).…”
Section: Resultsmentioning
confidence: 99%
“…different spatial and temporal scales), making difficult to summarize the findings [ 3 ]. Malaria transmission varies widely within and across countries as the micro-epidemiological variation of malaria is related to fine-scale heterogeneity in environmental, genetic, social, and other contextual factors [ 56 ].…”
Section: Discussionmentioning
confidence: 99%